2009
DOI: 10.2334/josnusd.51.437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial activity of three cements: new endodontic cement (NEC), mineral trioxide aggregate (MTA) and Portland

Abstract: Using the agar diffusion method, we conducted an in vitro study to evaluate the antimicrobial activity of mineral trioxide aggregate (MTA), new endodontic cement (NEC) and Portland cement at different concentrations against five different microorganisms. A base layer was made using Muller-Hinton agar for Escherichia coli (ATCC 10538) and Candida (ATCC 10231). For Actinomyces viscosus (ATCC 15987), Enterococcus faecalis (ATCC 10541) and Streptococcus mutans (ATCC 25175) blood agar medium was used. Wells were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
3
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
3
31
3
1
Order By: Relevance
“…However, in this study all materials were ineffective against E. faecalis, as similar to those observed in the literature related to Estrela et al 4 , Ribeiro et al 13 , Zarrabi et al 14 and Miyagak et al 24 , in constrast to the results presented in Sipert et al 11 and Tanumaru Filho et al 12 investigations.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, in this study all materials were ineffective against E. faecalis, as similar to those observed in the literature related to Estrela et al 4 , Ribeiro et al 13 , Zarrabi et al 14 and Miyagak et al 24 , in constrast to the results presented in Sipert et al 11 and Tanumaru Filho et al 12 investigations.…”
Section: Discussionsupporting
confidence: 73%
“…The antimicrobial effect of MTA and PC measured the test of inhibition in agar was already observed against microorganisms [13][14][15] . However, no previous studies have evaluated the antimicrobial activity exclusively against bacterial strains of deep decayed dentin [16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that rootend filling materials are placed in small cavities (3-mm deep), their properties should ideally include good adhesion to dentine walls and biocompatibility (6). The methodology employed in this study was based on that of previous investigations using the in vitro microbial leakage model (2,4,5). Despite the restraint of leakage study methodology (5), dye and radioisotope leakage models have limitations such as the molecular size of most dye particles being smaller than that of bacteria and these models do not reproduce the interactions between microbial and non-microbial tracers (17).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal properties of root-end filling include optimal apical seal, biocompatibility, adhesiveness to dentine walls and microbial control. Several materials have been recommended for root-end filling, including gutta-percha, amalgam, ZOE cement, Cavit, composite resins, glass ionomers, Super-EBA and mineral trioxide aggregate (MTA) (1)(2)(3)(4)(5). Mineral trioxide aggregate, developed at Loma Linda University, USA, has been indicated for sealing off the pathways of communication between the root canal system and the outer surface of the tooth (1,7).…”
Section: Introductionmentioning
confidence: 99%
“…CEM cement has a pH value similar to that of MTA; however, it has higher fluidity as compared to MTA with shorter working time and less film thickness . A study by showed that CEM has antimicrobial activity against pathogens, similar to that of calcium hydroxide and better than that of MTA (Asgary and Kamrani, 2008;Zarrabi et al, 2009). Antifungal effects of MTA and CEM against Candida albicans have been compared and it has been shown that both materials completely destroy the fungus in 24 h…”
Section: Introductionmentioning
confidence: 99%